Terapi Musik: Bebas Budaya atau Terikat Budaya? - Alma Marikka Geraldina (Faculty of Psychology Universitas Gadjah Mada, 2017)
Music therapy began to show its existence as one of the new therapeutic methods. Music therapy which was previously identic with Western society, is now starting to be used in Indonesia. It began to develop as one of therapy methods in psychology field. Along with the development of music therapy, the issues around music therapy are also an interesting study material. Newly developed music therapy in Indonesia often has very different application methods between one and another study, and the use of music as a method of therapy is still being debated issue to find good operational standards. Therefore, this paper attempts to examine the growing cultural-related assumptions around music and music therapy.